Students’ and Teacher’s Perceptions on Zoom Application in English Language Learning - Lie, Eka Rismaningsih; Anwar, Choiril; Widiyati, Elok (Journal of Advanced Multidisciplinary Research, 2024)
The purpose of this research was to find out EFL students’ and teacher’s perceptions of the effectiveness of Zoom applications in English language learning. Qualitative descriptive was used in this research. In this research, 68 students from two classes in grade 11 at SMAN 1 Fakfak in the 2022-2023 school year were used as the subjects of the study. Questionnaires and interviews were used to collect data. According to the results of the questionnaires that were distributed, it shows that from 17 statements of the questionnaires, 14 statements got a positive perception, 2 statements got a negative perception, and 1 statement got a neutral perception of the effectiveness of Zoom application in English language learning. Interviews with 10 students and an English teacher show that 7 students showed a positive opinion, 2 students showed a negative opinion, and one student showed a neutral opinion, while the English teacher showed a positive opinion toward the interview’s question related to the effectiveness of Zoom application in English language learning. The research concluded that EFL students and the teacher at SMAN 1 Fakfak generally approved that the Zoom application was simple to use, interesting, and fun, and had a positive impact on students during English language learning activities.